KEANEKARAGAMAN DAN KELIMPAHAN JENIS SATWA BURUNG DI PULAU GOROM KABUPATEN SERAM BAGIAN TIMUR - Jasna Hanubun; Maya M. S. Puttileihalat; John F. Sahusilawane (MARSEGU : Jurnal Sains dan Teknologi, 2026)
Gorom Island, located in East Seram Regency, is one of the areas with significant biodiversity potential; however, information regarding bird diversity and abundance in this region is still limited. This study aimed to determine the levels of diversity, evenness, and abundance of bird species across three habitat types, namely mixed forest, secondary forest, and mangrove forest. The research was conducted in June 2023 using the Index Ponctuel d’Abondance (IPA) method through direct observations at designated points during morning and afternoon periods. Data were analyzed using the Shannon-Wiener diversity index, evenness index, and relative abundance. The results showed that a total of 18 bird species belonging to 10 families were identified. The diversity index values were categorized as moderate across all habitat types, with secondary forest (H’ = 2.58), mixed forest (H’ = 2.21), and mangrove forest (H’ = 1.59). The evenness index in all habitats indicated stable conditions, reflecting a relatively even distribution of individuals. The highest species abundance was found in secondary forest with 14 species and 121 individuals, followed by mixed forest with 10 species and 102 individuals, and mangrove forest with 8 species and 50 individuals. These findings indicate that all habitat types are still capable of supporting bird life, with secondary forest being the most optimal habitat.